The Darling diaries : memoirs of a political career - Darling, Stan, 1911- (Dundurn Press, 1995)
A stalwart Tory, Stan Darling was a Member of Parliament for twenty-one years. In The Darling Diaries, he looks back on his career in politics, the places he has been, and some of the poeple he has met -- Libyan dictator Gaddafi, President Bush, and Maharishi Mahesh Yogi. Never afraid of the press or anyone else foolish enough to quarrel with him, he strenuously advocated (and got) controls on the emmissions which cause acid rain -- for which he earned the nickname Mr. Acid Rain. He helped to get a free vote on the death penalty in Parliament. Whether in his native Burks Falls, Ontar.